Detection and Quantification of Neurotransmitters in Dialysates. Issue 1 (1st April 2013) - Zapata, Agustin; Chefer, Vladimir I.; Parrot, Sandrine; Denoroy, Luc
Abstract: Sensitive analytical methods are needed for the separation and quantification of neurotransmitters obtained in microdialysate studies. This unit describes methods that permit quantification of nanomolar concentrations of monoamines and their metabolites (high‐performance liquid chromatography [HPLC] electrochemical detection), acetylcholine (HPLC‐coupled to an enzyme reactor), and amino acids (HPLC‐fluorescence detection, capillary electrophoresis with laser‐induced fluorescence detection). Curr. Protoc. Neurosci . 63:7.4.1‐7.4.35. © 2013 by John Wiley & Sons, Inc.